Reference values for and determinants of right atrial area in healthy adults by 2-dimensional echocardiography - Grünig, Ekkehard; Henn, Philipp Christian; Benjamin, Nicola; Maier, Felicitas Carolin; Prange, Felix; Weidenhammer, Johannes; Fischer, Christine (Circulation. Cardiovascular imaging, 2013)
Background—Right atrial (RA) size is important in screening, diagnosis, and follow-up assessment in patients with pulmonary hypertension. The objective of this study was to define normal reference values for RA area by echocardiography in a large population of athletic versus sedentary healthy subjects.Methods and Results—In the first part of the study, 880 healthy adult subjects (mean age, 28±6 years; 38% women; 395 top-level endurance athletes, 255 strength athletes, and 230 nonathletes) were prospectively assessed. In the second part, we performed a pooled analysis of all studies published between 1976 and 2011 describing RA area in healthy subjects (n=624). Statistical analysis included the calculation of 95% quantiles for defining cutoff values. Mean RA area in the 880 subjects was significantly larger in endurance athletes compared with the strength athletes and nonathletes. RA area correlated significantly with age, sex, body surface, and endurance training. In a synopsis of both data sets, 95% quantiles for RA area in strength atheletes and nonathletes were 15.2 cm2 (95% confidence interval, 14.7-15.7) in women and 16.2 cm2 (95% confidence interval, 15.8-16.6) in men.Conclusions—To the best of our knowledge, this is the largest data set to describe RA size in adult healthy subjects (age <50 years). Cutoff values for RA area were significantly different in women (15 cm2) and men (16 cm2). Age, sex, body surface area, and high-level endurance training were determinants of RA area.